A Rare Case of Leiomyosarcoma of Inferior Vena Cava Managed with Curative Resection and PTFE Vascular Graft Reconstruction: A case report with review of literature - Gori, Jayesh; Manyath, Nithya; Bhaduri, Debanshu; Bhatia, Manish (International Journal of Medical Research and Review, 2014)
Primary vascular leiomyosarcoma is rare tumour arising most frequently from inferior vena cava. In literature only case reports or small case series are available. The presentation and surgical management depends on origin of the tumour in relation to the hepatic and renal veins, tumour growth (extra luminal or intra luminal) and involvement of surrounding structures. Leiomyosarcoma of inferior vena cava tumour poses a challenge with respect to resectability, reconstruction, potential for massive haemorrhage, requirement of cardiopulmonary bypass and possibility of tumour thromboemboli. Our experience with successful management of rare case and with thorough literature review suggest surgical resection of leiomyosarcoma of the IVC with Polytetrafluoroethylene vascular graft reconstruction provides good surgical and oncological outcome.